Curriculum and Learning System Adapted at the Khalaf Islamic Boarding Schools: An Educational Perspective - Suhartini, Andewi; Hidayat, Yusuf; Basri, Hasan (International Journal Corner of Educational Research, 2024)
Islamic boarding schools are Islamic educational institutions that have a significant role in character formation and intellectual development of the young generation of Muslims in Indonesia. Today, Islamic boarding schools are divided into two main categories: Salaf (traditional) Islamic boarding schools and Khalaf (modern) Islamic boarding schools. This study aims to identify the curriculum and learning system at the Khalaf Islamic boarding school, which combines religious education with general education in order to prepare students to face the challenges of the globalization era. The results of the study show that Khalaf Islamic boarding schools not only maintain religious learning through traditional methods such as sorogan and bandongan, but also adopt modern learning systems, including formal classes and technology integration. The Khalaf Islamic boarding school curriculum consists of religious and general curriculums, which are designed in balance between religious knowledge and contemporary science. In conclusion, the Khalaf Islamic boarding schools offer an adaptive educational model in line with the demands of the era and needs of society in the digital era without losing the noble characters as the identity of Islam.